A new spectrofluorometric method for pyrophosphate assay based on the fluorescence enhancement of trypsin-stabilized copper clusters. Issue 2 (3rd December 2014) - Wang, Wei; Zhan, Lei; Du, Yu Qing; Leng, Fei; Huang, Cheng Zhi
Abstract : A new method for pyrophosphate detection in aqueous solution has been developed based on the fluorescence enhancement of trypsin-stabilized CuNCs. Abstract : A novel and selective spectrofluorometric method for pyrophosphate (PPi) assay in aqueous solution was developed in this contribution on the basis of the enhanced fluorescence intensity of trypsin-stabilized copper clusters (CuNCs). Mechanism investigation showed that PPi can make the CuNCs dispersed, concomitantly resulting in the improved quantum yield and the enhanced fluorescence emission of the CuNCs. A good linear relationship in the range of 78 μM–20 mM was achieved between the enhanced fluorescence intensity of the CuNCs at 455 nm and the logarithm of PPi concentration with the detection limit (3 σ ) of 101 nM. By this approach, we can achieve simple, fast and inexpensive detection of PPi.